An Evaluation of the Use of Performance Measures in Health Care - Damberg, Cheryl L. (RAND Corporation, 2011)
This report presents the results of an evaluation of health care performance measures, describes how performance measures are being used by a wide array of organizations and the types of measures being used for different purposes, summarizes key barriers and facilitators to the use of measures, and identifies opportunities for easing the use of performance measures moving forward.